PERAN TEOLOGI DALAM PEMBENTUKAN KARAKTER MAHASISWA KRISTEN - Agni Domince Banunaek (JIP: Jurnal Ilmu Pendidikan, 2025)
Character formation is one of the most important aspects of education, especially for Christian students who are being prepared to become leaders, servants, and responsible members of society. Theology is not merely a study about God, but also a foundation of values that shapes a person’s attitude, mindset, and behavior. Through sound theological teaching, Christian students can understand who God is, who they are before God, and how they should live in this world. Theology teaches values such as love, honesty, responsibility, and self-sacrifice all of which are essential in building strong and healthy character. This journal aims to explain how theology actively contributes to character formation among Christian students, both through formal education and spiritual experiences in the faith community. By understanding the role of theology more deeply, Christian students are expected to integrate their faith into daily life in a real and relevant way.